Patients and healthcare workers experience with a mobile application for self-management of diabetes in Qatar: A qualitative study - Abd-alrazaq, Alaa A.; Suleiman, Noor; Baagar, Khaled; Jandali, Noor; Alhuwail, Dari; Abdalhakam, Ibrahem; Shahbal, Saad; Abou-Samra, Abdul-Badi; Househ, Mowafa (Computer methods and programs in biomedicine update, 2021)
•Mobile health solutions may play a crucial role in improving patients’ self management of diabetes.•Patients and educators show a positive opinion of mobile health solutions as a way of communicating with each other.•Cultural beliefs and values affect patient attitudes towards m-health solutions.•The continuing use of mobile health interventions is a crucial factor in its long-term viability and eventual success. Diabetes mellitus (DM) is highly prevalent in the Middle East and North Africa (MENA) region. Mobile health (m-health) can improve communications between diabetic patients and medical teams, and this, in turn, may enhance engagement and self-management. Droobi is a multi-language mobile application designed to support self-management of patients with DM. The study aimed to explore experiences of patients and educators about their communication before and after implementation of Droobi, a diabetes management app. We interviewed a convenience sample consisting of 9 patients and 5 nurse educators. Before interviews, Droobi was downloaded to participants’ mobile phone, and their profile on the application was created. To ensure optimum usage experience, all participants received education on how to use Droobi. Participants used Droobi for 6 to 12 weeks. All interviews were audio recorded, transcribed by professionals, and thematically analyzed. Two main themes were generated from participants’ responses. The first theme relates to experiences of patients and educators about their communication before Droobi and consists of 3 sub-themes: (1) how patients communicated with medical team before Droobi (previous methods), (2) adoption of previous communication methods, and (3) shortcomings of previous communication methods. The second theme relates to experiences of patients and educators about their communication after Droobi and consists of 4 sub-themes: (1) adoption of Droobi, (2) advantages of Droobi, (3) shortcomings of Droobi, and (4) improvements suggested by educators and patients. Our findings suggest that Droobi provided a more efficient and convenient way for communication between health workers and patients, yet multiple shortcomings and several suggestions for improvements were noted. Future work should continue evaluating the Droobi app, they should include a number of different stakeholders when developing the upcoming Droobi version taking into account the limitations and suggestions put forth by the end-users.